Providing Choice in Middle Grade Classrooms: An Exploratory Study of Enactment Variability and Student Reflection. (May 2016) - Williams, Jasmine D.; Wallace, Tanner LeBaron; Sung, Hannah C.
Employing descriptive and interpretive analyses of classroom videos and focus group data, this study details how the provision of choice was enacted in instruction, and the subsequent messages students perceived. Participants included six teachers (fourth to eighth grade) and 114 students (ageX ¯ = 11.28 years, 60% African American). Survey data indicated students perceived high levels of choice in the focal classrooms (Time 1X ¯ = 3.32, SD = 0.91; Time 2X ¯ = 3.25, SD = 0.94). Results suggest five differentiating dimensions of providing choice: strategy, pace, format, topic, and mobility as well as differences in the structure of how choice was provided—a single event versus a generative sequence of autonomy-supportive adolescent-teacher interactions. Analysis of student focus group transcripts indicated the enactment of choice communicated messages around trust, respect, and worth that influenced student engagement. Overall, results suggest the provision of choice can be a context for meeting young adolescents' developmental needs and fostering students' motivational resources.